A review of the functionalities of smart walkers. Issue 10 (October 2015) - Martins, Maria; Santos, Cristina; Frizera, Anselmo; Ceres, Ramón
Highlights Importance of smart walkers. Studies related to the concept of autonomous and shared-control and manual guidance. The use of smart walkers as personal helpers to sit-to-stand. Diagnostic tools for patients' rehabilitation through the evaluation of their gait.